Rabindranath Tagore and World Literature - Acharya, Pushpa Raj (Literary Studies, 2015)
Courses on world literature in English translations indicate to a new popular trend in the discipline of comparative literature in North American universities. Some scholars like David Damrosch promote the practice as a new way of doing comparative literature, but others like Gayatri Chakravorty Spivak think that an encyclopedic survey of world literatures in English translations confirms the logic of globalization. Whether the world literature courses and anthologies in English translation inspire enthusiasm or invite reservation, the question "What is world literature?" has come to the fore as one of the central concerns of the discipline. In 1907, eighty years after German poet Johann Wolfgang von Goethe in Germany coined the term Weltliteratur, Rabindranath Tagore in India expressed his views on “comparative literature” translating it as vishwa sahitya, “world literature.” My paper is a reading of Tagore’s lecture on world literature. Tagore envisions world literature as a creative transgression that activates a persistent human struggle for a bonding between aesthetics and alterity.